2015
DOI: 10.1016/j.medici.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Management of coronary artery disease patients in Latvia compared with practice in Central-Eastern Europe and globally: Analysis of the CLARIFY registry

Abstract: Latvian CAD patients are well managed in terms of aspirin use and frequency of percutaneous coronary intervention. Control of obesity and high BP is poorer and needs further improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Risk factors found in Austrian outpatients with stable CAD were smoking, overweight, hypertension, raised LDL cholesterol plasma levels, elevated heart rate and a low level of physical activity [ 16 , 18 ]. Anginal symptoms were more common in women than in men, which is consistent with the data of the whole CLARIFY population as well as the Euro Heart Survey [ 16 , 20 , 21 ]. It was shown that women present with angina twice as often as men [ 17 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Risk factors found in Austrian outpatients with stable CAD were smoking, overweight, hypertension, raised LDL cholesterol plasma levels, elevated heart rate and a low level of physical activity [ 16 , 18 ]. Anginal symptoms were more common in women than in men, which is consistent with the data of the whole CLARIFY population as well as the Euro Heart Survey [ 16 , 20 , 21 ]. It was shown that women present with angina twice as often as men [ 17 ].…”
Section: Discussionsupporting
confidence: 88%
“…In this context, the registry includes symptomatic and asymptomatic patients. The main objectives were to define contemporary patients with stable CAD, to identify discrepancies between evidence-based recommendations and practice, and to investigate long-term prognostic determinants [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Local data are very important to develop country-specific management programs for CV patients [ 40 ]. However, previous largest studies on CV risk factors prevalence in Latvian population have not assessed depression and anxiety as possible risk factors [ 36 , 72 , 73 ]. Findings of this study suggest that detection and treatment of depression should be included in CV patients` management programs and future research on CV risk factors in Latvia.…”
Section: Discussionmentioning
confidence: 99%
“…Very relevant factors of AMI care are time for early diagnosis, the fastest reperfusion time, and the use of different types of medications (antiplatelet agents, antihypertensives, antianginal drugs, and lipid-lowering drugs) [8,9,10,11,12]. Previous surveys from some European countries estimated an enrichment in coronary care, accentuating improve of invasive diagnostics and treatment procedures, and an extensive use of varies medications [6,13,14,15,16,17]. Meanwhile, there was no observed marked improvement in short- or long-term survival among persons who had experienced AMI in Lithuania or other Baltic countries [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there was no observed marked improvement in short- or long-term survival among persons who had experienced AMI in Lithuania or other Baltic countries [13,18]. The latest data of coronary care quality and mortality trends due to AMI in Central and Eastern European countries showed lack of similar data on extensive changes of acute coronary care in these countries [17,19]. According to official Lithuanian mortality statistics, every eighth death from ischemic heart disease occurs in persons of working (25–64 years) age, of whom even a quarter in working age men [1].…”
Section: Introductionmentioning
confidence: 99%